The Implementation of Finger Puppet Learning Media to Enhance Student Learning Interest in Indonesian Language Lessons for Grade IV at Madrasah Ibtidaiyah Sungai Undan - Diki Fauzi Agustria; Andi Nurhasanah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The lack of attention of fourth-grade students at Madrasah Ibtidaiyah Sungai Undan during the learning process makes them unable to concentrate and feel less interested in learning. Therefore, this study was conducted to understand the increase in learning interest of fourth-grade students in Indonesian language subjects by using finger puppets as learning media. This study adopted the Classroom Action Research (CAR) method. There were two cycles in this study, each consisting of four steps, namely planning, implementation, observation, and reflection. The data collection techniques in this study used observation, interviews, questionnaires, and documentation. The results of the study showed that the average learning interest of students in the pre-cycle was 58.08 out of the total number of students. After the action was implemented in cycle I, the average increased to 70.1, and after cycle II, the results showed a significant increase with an average of 81.23.